The Integration of Gender Perspective into Young People's Sexuality Education in Spain and Portugal: Legislation and Educational Models - Oliveira, Aliete Cristina Gomes Dias Pedrosa da Cunha (2021)
Throughout history, Sexuality Education (SE) has undergone many changes in formal education curricula. The education systems should incorporate SE and promote an understanding of sexuality from the critical perspective of gender. Objectives: To examine the approach to SE in young people in Spain and Portugal, considering the incorporation of the gender perspective, and analyze the legislation in both countries. A scoping review was conducted considering studies with SE programs, gender perspective, and legislation in Spanish, Portuguese, and English, without any time limits. The population consisted of young people aged 10 to 18 years who did not attend higher education. Databases used: CINAHL Complete, ERIC, LILACS, SciELO, MEDLINE, Psychology and Behavioral Sciences Collection, Scopus, Open Access Scientific Repository of Portugal, Base de Datos de Tesis Doctorales, Theses and Dissertations Online, and governmental websites. Thirty-two studies were found, including intervention, diagnosis, and documental programs. Eight of the studies adopted the gender perspective. Legislation in both countries is vast, with 23 main references. Although SE is legislated in both countries, the social-health and educational programs are insufficient. The relevance of the gender perspective is not incorporated into SE.